A Study on Adsorption Refrigerator Driven by Solar Collector Using Indonesian Activated Carbon - Tulus B. Sitorus; Farel H. Napitupulu; Himsar Ambarita (Journal of Engineering and Technological Sciences, 2017)
In the present work, the performance of an adsorption refrigerator driven by a solar collector was investigated. The adsorbent used in this study was 6.5 kg ordinary granular activated carbon of coconut shell produced in the Sumatera Utara province of Indonesia, 3 liters of methanol as adsorbate and 4.5 litres of water as the medium that was cooled. The experiments were carried out under varying weather conditions during seven cycles with total solar radiation about 2.681-3.918 kWh/m2/cycle. In this study, the values of the coefficient of performance (COP) obtained were about 0.0827-0.1271. The values of specific cooling power (SCP) obtained were in the range of 0.01839-0.01883 kW/kg. The experimental results show that the adsorption refrigerator system can deliver an evaporator temperature of about 2.81-13.61°C.